2016
DOI: 10.1016/j.aquatox.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alkylphenols on the biotransformation of diuron and enzymes involved in the synthesis and clearance of sex steroids in juvenile male tilapia ( Oreochromus mossambica )

Abstract: Previous studies using in vivo bioassay guided fractionation indicated that the herbicide diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) and alkylphenol (AP)-containing surfactants were detected in fractions of extracts that induced the estrogenic biomarker, vitellogenin in fish exposed to surface water extracts from the United States. However, when the compounds were evaluated individually using in vivo estrogenic assays or in vitro estrogen receptor assays, estrogenic activity was not observed. Since APs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Then, Pereira et al (2016) demonstrated that diuron metabolites, but not diuron, have estrogenic effects in female Nile tilapias, evidenced by increased estradiol (E 2 ) plasma levels, gonadosomatic indices and elevated percentage of final vitellogenic oocytes, despite decreasing the amount of germinative cells. Felício et al (2015) further showed that exposure of Nile tilapia to diuron and its metabolites at similar concentrations in combination with alkylphenols resulted in increases in vitellogenin levels and decreased testosterone levels, confirming the estrogenic and anti-androgenic effects of diuron and its metabolites in fish.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Then, Pereira et al (2016) demonstrated that diuron metabolites, but not diuron, have estrogenic effects in female Nile tilapias, evidenced by increased estradiol (E 2 ) plasma levels, gonadosomatic indices and elevated percentage of final vitellogenic oocytes, despite decreasing the amount of germinative cells. Felício et al (2015) further showed that exposure of Nile tilapia to diuron and its metabolites at similar concentrations in combination with alkylphenols resulted in increases in vitellogenin levels and decreased testosterone levels, confirming the estrogenic and anti-androgenic effects of diuron and its metabolites in fish.…”
Section: Introductionmentioning
confidence: 77%
“…Diuron, another phenylurea herbicide extensively used worldwide for weed control was also found in surface waters at concentrations up to 200 ng/L in the San Francisco Bay-USA (Schlenk et al, 2012). Based on this information, studies regarding alterations in sexual hormones and gametogenesis in tilapias were previously done by our group, using 40, 100 and 200 ng/L od diuron (Pereira et al, 2015(Pereira et al, , 2016Felício et al, 2015;Boscolo et al, 2017). Therefore, tebuthiuron concentrations used in this study was chosen considering realistic tebuthiuron concentration found in natural environments but also considering other studies previously published by our laboratory with diuron, for comparative purposes.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Felício et al [34], it was observed that Diuron has shown to antagonize estrogenic and androgenic receptors of steroid hormones which can potentially impair the gonadal steroidogenesis and the reproductive system of teleosts. Diuron has also shown to be anti-androgenic, inducing vitellogenin in juvenile male tilapia (Oreochromis mossambica) [35] and anti-androgenic compounds (AAC) with key enzymatic activities [36]. Another effective herbicide called Atrazine also demonstrated the reduction in the reproduction of Japanese medaka (O. latipes) [29] and fathead minnow (Pimephales promales) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Alkylphenol ethoxylates and alkylphenols enhanced the estrogenic activity of diuron in male Fathead Minnows . Subsequent studies in male tilapia also indicated the induction of cytochrome P450 by nonylphenol ethoxylates (NPE) and nonylphenols NPs, presumably enhancing the formation of more active metabolites of diuron such as 3,4-dichlorophenyl-N-methylurea (DCPMU), which was more potent than the parent compound, diuron, in males and females (Felicio et al 2016;Pereira et al 2016). Anti-androgenic activity was also noted in males, in addition to the estrogenic responses that indicate multiple targets that result in overall feminization (Pereira et al 2015).…”
Section: Approaches Used To Understand Effects Of Chemical Mixtures Amentioning
confidence: 99%